Correlation between dental and oral health knowledge and dental caries status through the HI BOGI application in elementary school children aged 11–12 years: Study cross-sectional - Fadilah, Rina Putri Noer; Endro, Hartanto; Hizami, Muhammad Rifqi (Padjadjaran Journal of Dental Researchers and Students, 2026)
ABSTRACTIntroduction: Dental caries is a common disease in Indonesia, with a prevalence of 82.8%. School-aged children, especially elementary school students, generally have relatively low levels of knowledge about dental and oral health. This study aimed to analyze the correlation between dental and oral health knowledge and caries status in children aged 11-12 years in Cimahi City, through the use of the HI BOGI application. Methods: This study was a quantitative study with a cross-sectional design involving 300 public elementary school children aged 11-12 years from 9 selected schools in Cimahi City. The sample was selected using a cluster random sampling technique in three sub-districts, namely Central Cimahi, South Cimahi, and North Cimahi, followed by proportional sampling. Sample size determination was performed using a two-proportion hypothesis test formula based on sample size software, with a minimum of 250 respondents and a target of 290 respondents. Inclusion criteria included students aged 11-12 years who were actively registered and willing to participate, while exclusion criteria included absence during the study, as well as incomplete photo documentation. Data were collected using the HI BOGI application and a Google Form questionnaire, then analyzed using the Spearman correlation test. Results: The level of children's knowledge was in the high category with an average value of 13.55 ± 1.90, while the dental caries status was classified as low with an average DMF-T index value of 2.53 ± 1.80. The Spearman correlation test showed a value of r = -0.60 with p = 0.302, which indicates that there is no significant correlation between the level of knowledge and dental caries status. Conclusion: There is no correlation between oral health knowledge and dental caries status in children aged 11-12 years in Cimahi City based on the use of the HI BOGI application.KEY WORDS:  elementary school children, HI BOGI, DMF-T index, dental caries, knowledgeKorelasi pengetahuan kesehatan gigi dan mulut terhadap status karies gigi melalui aplikasi HI BOGI pada anak SD usia 11-12 tahun: Studi cross-sectionalABSTRAKPendahuluan: Karies gigi merupakan penyakit yang umum di Indonesia, dengan prevalensi mencapai 82,8%. Anak usia sekolah, khususnya siswa sekolah dasar, umumnya masih memiliki tingkat pengetahuan yang rendah mengenai kesehatan gigi dan mulut. Penelitian ini bertujuan menganalisis korelasi antara pengetahuan kesehatan gigi dengan status karies pada anak usia 11-12 tahun di Kota Cimahi, menggunakan aplikasi HI BOGI. Metode: Penelitian ini merupakan studi kuantitatif dengan desain cross-sectional yang melibatkan 300 anak Sekolah Dasar Negeri usia 11-12 tahun dari 9 sekolah terpilih di Kota Cimahi. Sampel dipilih menggunakan teknik cluster random sampling pada tiga kecamatan, yaitu Cimahi Tengah, Cimahi Selatan, dan Cimahi Utara, yang dilanjutkan dengan proportional sampling. Penentuan jumlah sampel dilakukan menggunakan rumus uji hipotesis dua proporsi berdasarkan perhitungan software sample size, dengan jumlah minimal 250 responden dan target 290 responden. Kriteria inklusi meliputi siswa usia 11-12 tahun yang terdaftar aktif dan bersedia menjadi responden, sedangkan kriteria eksklusi meliputi ketidakhadiran saat penelitian, dan ketidaklengkapan dokumentasi foto. Data dikumpulkan menggunakan aplikasi HI BOGI dan kuesioner Google Form, kemudian dianalisis dengan uji korelasi Spearman. Hasil: Tingkat pengetahuan anak berada pada kategori tinggi dengan nilai rerata 13,55  1,9, sedangkan status karies gigi tergolong rendah dengan nilai rerata indeks  DMF-T 2,53  1,8. Uji korelasi  Spearman menunjukkan nilai r=-0,60 dengan p = 0,302, yang mengindikasikan tidak terdapat korelasi yang signifikan antara tingkat pengetahuan dan status karies gigi. Simpulan: Tidak terdapat korelasi antara pengetahuan kesehatan gigi dan mulut dengan status karies gigi pada anak usia 11-12 tahun di Kota Cimahi melalui penggunaan aplikasi HI BOGI. KATA KUNCI: anak SD, HI BOGI, indeks DMF-T, karies gigi, pengetahuan